IN VITRO EFFECTS OF ORGANIC ACID AND PLANT OILS ON SHEEP RUMEN FATTY ACID COMPOSITION - Z. Váradyová; K. Mihaliková; T. Laho; S. Kišidayová; D. Jalč (Journal of Animal and Plant Sciences, 2013)
The effects of diets (i.e., high fibre, HF and high concentrate, HC) supplemented with either fumaric acid (FUM; 8 mmol/L) or maleic acid (MAL; 8 mmol/L) and different plant oils (35.0 g/kg dry matter; sunflower, SO; rapeseed, RO; and linseed, LO) on rumen sheep fatty acids (FA) concentration and biohydrogenation (BH) in batch cultures were examined. The oils rich in linoleic acid (SO, 535 g/kg of FA), oleic acid (RO, 539 g/kg of FA) and α-linolenic acid (LO, 538 g/kg of FA) were examined. The diets and organic acids with oils (AO) affected the concentration of almost all FA in batch cultures. Compared with the control, higher concentrations of trans-vaccenic acid occurred for the HF-diet with FUM+SO and MAL+SO (P<0.001) and for HC-diet with FUM+SO, MAL+SO, FUM+RO and MAL+RO (P<0.01 and P<0.001). The BH of oleic acid in both the HF- and HC-diets with organic acids and oils was decreased when compared with the control. The combination of FUM and MAL, especially with SO and RO, might positively enhance the concentration of FA and some FA intermediates and decreases the BH of C18 FA in rumen fluid in batch cultures.
Keywords: batch cultures; fumaric acid; maleic acid; sunflower oil; rapeseed oil; linseed oil; sheep rumen